2010
DOI: 10.1002/cncr.24915
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous but not clear cell histology is associated with inferior survival in patients with advanced stage ovarian carcinoma treated with platinum‐paclitaxel chemotherapy

Abstract: BACKGROUND: Mucinous and clear cell histology have been associated with adverse prognosis in ovarian carcinomas. The authors compared the outcome of these subtypes with that of serous tumors in patients who were treated with combination paclitaxel/platinum at their center. METHODS: Four hundred twenty patients with histologically confirmed, serous (n ¼ 367), mucinous (n ¼ 24), or clear cell (n ¼ 29) ovarian carcinomas, International Federation of Gynecology and Obstetrics stage III or IV disease, and who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 19 publications
3
53
0
Order By: Relevance
“…EOC tumors are generally classified into histological subgroups depending on their aggressive behavior and their malignant potential (D'Andrilli et al 2008;Lalwani et al 2011). EOC classification becomes of interest during the planning of treatment and management as studies show that the different subtypes respond differently to treatment regimens (Bamias et al 2010). Further investigations into new predictive biomarkers that can identify subpopulations of patients who are most likely to respond to a given therapy should aid in EOC disease control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EOC tumors are generally classified into histological subgroups depending on their aggressive behavior and their malignant potential (D'Andrilli et al 2008;Lalwani et al 2011). EOC classification becomes of interest during the planning of treatment and management as studies show that the different subtypes respond differently to treatment regimens (Bamias et al 2010). Further investigations into new predictive biomarkers that can identify subpopulations of patients who are most likely to respond to a given therapy should aid in EOC disease control.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mucinous adenocarcinoma are considered to be refractory cancers that are biologically distinct from serous adenocarcinoma, and some studies suggest that mucinous tumors present a poorer outcome from platinum-based first-line chemotherapy when compared to non-mucinous epithelial ovarian cancers (Bamias et al 2010;Sugiyama et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, advanced MAC has a poorer prognosis than other histopathologic subgroups (6). MAC's low response (26-42%) to conventional platinum-based chemotherapy is associated with a poor prognosis because chemosensitivity is one of the main prognostic factors for patients with advanced EOC (7)(8)(9)(10). Although MAC is known to be resistant to platinum/taxane combination chemotherapy (10), patients with MAC are usually treated with this first-line chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to serous adenocarcinoma (SAC), which is the most common histopathologic subgroup of EOC, MAC is relatively resistant to the conventional platinum or taxane-based chemotherapy, thereby leading to a poor prognosis (7)(8)(9)(10). It has been reported that MAC differs from SAC pathologically and cytogenetically, and more closely resembles colorectal cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Certain histologic subtypes of epithelial ovarian cancer, such as mucinous and clear cell variants, have been suggested to demonstrate a chemoresistant phenotype [57,58]. A study based on a Japanese population-based cancer registry showed that in women older than 50 years, an increasing trend in clear cell, mucinous, and endometrioid adenocarcinomas was observed over a 24-year period from 1983 to 2007.…”
Section: More Aggressive Disease?mentioning
confidence: 99%